Smart Sport Watch Usage: The Dominant Role of Technology Readiness over Exercise Motivation and Sensation Seeking - Gershon Tenenbaum; Tomer Ben-Zion; Yair Amichai-Hamburger; Yair Galily; Assaf Lev (Technologies)
The study examines the link between technology readiness/acceptance, motivation for exercising, and sensation seeking and using or avoiding Smart Sport Watches (SSW). A sample of 315 adolescents, Mage = 29.6 (SD = 11.01) and healthy male (n = 95, 30.2%) and female (n = 179, 56.85%), completed all the measures of these variables’ dimensions via the internet. Multiple followed by univariate analyses of variance (MANOVA, ANOVA) were performed for each of the study’s psychological dimensions and single variables. The two categorical factors (e.g., BS factors) were the use of SSW (yes/no) and walk/run (yes/no). Results revealed that adolescents using SSW rated themselves significantly (p < 0.05) and substantially higher than their non-SSW users on positive readiness for technology (d = 0.47), and specifically on optimism (d = 0.34) and innovation (d = 0.51). Moreover, users of SSW reported significantly (p < 0.05) and substantially lower negative readiness for technology than their non-SSW users’ counterparts (d = −0.49), and specifically on discomfort (d = −0.38) and distrust (d = −50), but neither on the overall motivation for exercise dimensions nor on sensation-seeking. Moreover, adolescents who walk/run reported being more internally motivated (d = 0.38), integrated (d = 0.61), and identified (d = 0.34) than their sedentary counterparts. Discussion centers on the important role of readiness/acceptance in using technological devices and the need to use technology-specific motivation and personality measures to further explore this phenomenon.